Gambaran Usia, Paritas, Tingkat Pendidikan, Status Pekerjaan, Dukungan Suami dan Tingkat Pengetahuan Ibu dalam Pemberian ASI Eksklusif - Feling Polwandari; Sonia Wulandari (Faletehan Health Journal, 2021)
Exclusive breastfeeding is breastfeeding without any additional food for infants aged 0-6 months. Various studies showed that exclusive breastfeeding improves children's immunity and intelligence. Based on this fact, The Government gave recommendation through Health Minister Decision No. 450/MENKES/SK/VI/2004 about exclusive breastfeeding. However, not all mothers followed this recommendation. This study was conducted to determine the description of age, parity, education level, employment status, husband support, and maternal knowledge level in exclusive breastfeeding. This research is a descriptive study with case study by taking samples from Pelamunan Village as many as 54 respondents who have babies aged 0-6 months. The data collection was carried out by using a questionnaire of maternal characteristics and knowledge about exclusive breastfeeding. The results showed the majority of breastfeeding mothers are not at risk (84%), multiparity or grand multipara (77.5%), low education (83%), not working (77%), very supportive husbands (81%), and most breastfeeding mothers are knowledgeable (79%). Health officers were expected to do exclusive breastfeeding promotion to people of all circles and other researchers to answer the obstacles in the breastfeeding process by a better research method than descriptive.